Non-oral pharmacological interventions in the management of herpes zoster-related pain: a review of current research - Wang, Yaojun; Shen, Yanxia; Guo, Haixue; You, Dongcai; Jia, Shimin; Song, Ge; You, Xiaobing (Frontiers in Pain Research, 2024)
Herpes zoster-associated pain is a difficult-to-treat pathologic pain that seriously affects patients' quality of life. In recent years, emerging therapeutic techniques such as autologous platelet-rich plasma, sympathetic nerve block and pulsed radiofrequency have been gradually applied in the field of pain with the advantages of less trauma, quicker recovery and significant efficacy. These therapeutic options have become a new hope for the treatment of herpes zoster-associated pain. This article reviews the studies on herpes zoster-associated pain in non-oral drug therapy, summarizes the efficacy, safety, and possible mechanisms, and provides a reference basis for clinical treatment.